Evaluation of WASH Implementation in Nama Sub-County - Fernandes, Caroline; Flores, Claudia; Montalbano, Gabrielle; Sekhon, Harveen; Pierce, Dr. Gregory (Consilience, 2017)
Villages that had underwent GlobeMed and MCHI water access, sanitation, and hygiene (WASH) interventions tended to exhibit better sanitation and hygiene practices compared to control villages. Survey participants were directly recruited from households in eight rural villages that had previously received community-based WASH interventions in Nama sub-county, Uganda. All participants were adults (above eighteen) of varying ages and genders. The other participants were directly recruited from two rural villages who had not received any WASH intervention within Nama sub-county and served as our control groups. Participants were surveyed on various topics including water source quality and distance, prevalence of sickness, latrine management, and sanitation and hygiene practices. The effectiveness of WASH programs in GlobeMed and MCHI sponsored villages compared to control villages was measured using t-tests and Pearson Correlation Coefficients (R). Improved safe water and hygiene practices are fundamental to improving quality of life. Improved WASH related practices not only correlate with health, they ameliorate other frequently encountered inequities—like low school attendance—as education is a major factor in economic growth and alleviating poverty. Addressing WASH related problems can be challenging as they affect people from diverse communities and demographics. However, the most promising solutions arise when collaboration emerges between NGOs, governments, communities, and individuals.